2020
DOI: 10.1101/2020.07.07.20147967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An observational study identifying highly tuberculosis-exposed, HIV-1-positive but persistently TB, tuberculin and IGRA negative persons with M. tuberculosis specific antibodies in Cape Town, South Africa

Abstract: Background: Mycobacterium tuberculosis (Mtb) infection is inferred from positive results of T-cell immune conversion assays measuring Mtb-specific interferon gamma production (IGRA) or tuberculin skin test (TST) reactivity. Certain exposed individuals, termed resisters or early clearers, do not display T-cell immune conversion in these assays. Here we report a hitherto unknown extreme form of this phenotype: HIV-1-infected persistently TB, tuberculin and IGRA negative (HITTIN). Methods: A community-ba… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…One critical difference between the mouse model and humans is the ability of a subgroup of Mtb-exposed persons to avoid the development of classical T-cell immunity and TB disease even in the presence of long lasting Mtb exposure (9). Recently, the phenotype of strong resistance to immune conversion of persons living in high Mtb exposure settings has been confirmed for HIVinfected but immune-reconstituted people (21). While the underlying mechanisms that preclude the development of classical T cell immunity are unknown, initial results implicate both nonclassical T cells and B cells (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One critical difference between the mouse model and humans is the ability of a subgroup of Mtb-exposed persons to avoid the development of classical T-cell immunity and TB disease even in the presence of long lasting Mtb exposure (9). Recently, the phenotype of strong resistance to immune conversion of persons living in high Mtb exposure settings has been confirmed for HIVinfected but immune-reconstituted people (21). While the underlying mechanisms that preclude the development of classical T cell immunity are unknown, initial results implicate both nonclassical T cells and B cells (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the phenotype of strong resistance to immune conversion of persons living in high Mtb exposure settings has been confirmed for HIVinfected but immune-reconstituted people (21). While the underlying mechanisms that preclude the development of classical T cell immunity are unknown, initial results implicate both nonclassical T cells and B cells (21,22). How and where AM interact with these cells of the acquired immunity arm is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of the positive BAL and negative IGRA (wild dog 1) results could possibly suggest early infection, or recent inhalation of mycobacteria without infection; however, when opportunistically sampled 14 months after the positive BAL culture, this individual had a positive IGRA result, suggesting that this animal may have been infected at the time of the BAL sample and later developed immune sensitization. Studies have shown that Mycobacterium tuberculosis complex (MTBC) infection in other species (including humans) does not result in a positive IGRA result for all infected individuals (van der Heijden et al., 2020; Kroon et al., 2020; Nguyen et al., 2018). Negative immunoreactivity can either be indicative of a truly uninfected animal; an M. bovis infected animal in which a detectable immune response has not developed at the time of sampling (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, three out of seven subjects that produced these protective antibodies were IGRA negative. Another study from South Africa in HIV‐infected patients with no TB, and persistently negative TST/IGRA despite living in an area of TB hyperendemicity showed the presence of antibodies specific for Mtb 90 …”
Section: Mechanisms Of Bcg‐induced Protection Against M Tuberculosis Infectionmentioning
confidence: 99%
“…Another study from South Africa in HIV-infected patients with no TB, and persistently negative TST/IGRA despite living in an area of TB hyperendemicity showed the presence of antibodies specific for Mtb. 90 There are several potential mechanisms of antibody-mediated resistance against Mtb in the context of early clearance. Antibody could bind to Mtb bacteria to prevent entry into cells, drive antibodydependent cellular phagocytosis to increase bacterial killing, mediate antibody-dependent cellular cytotoxicity to kill infected cells, or mediate the recruitment of innate immune cells that express the Fc receptor.…”
Section: Antibody-mediated Resistancementioning
confidence: 99%